2022
DOI: 10.1002/ente.202100794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nickel Precursor on the Catalytic Performance of Graphene Aerogel‐Supported Nickel Nanoparticles for the Production of COx‐free Hydrogen by Ammonia Decomposition

Abstract: Graphene aerogel (GA), a promising porous material with high specific surface area and electrical conductivity, is utilized to disperse nickel nanoparticles to reach high catalytic activity in COx‐free hydrogen production from ammonia. Ni(NO3)2·6H2O and Ni (II) acetylacetonate (Ni(acac)2) were considered as metal precursors and the pH of the impregnation solution was varied to investigate the effects on the catalytic properties of the GA‐supported nickel catalysts. Data showed that the best dispersion and homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 87 publications
1
9
0
Order By: Relevance
“…Figure shows the representative SEM images of the pristine rGAs and IL-loaded rGAs. The clear, randomly oriented, wrinkled-sheet structures of pristine rGAs shown in Figure a,b are consistent with the previous reports. , The wrinkled nature of the composites prepared with rGA500 was more prominent compared to rGA300 composites, consistent with its higher surface area and pore volume. With the impregnation of ILs, rGAs became smoother by losing their roughness as can be seen in Figure c,d for [BMPyr]­[DCA] and Figure e,f for [BMPyr]­[PF 6 ]-loaded rGAs.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Figure shows the representative SEM images of the pristine rGAs and IL-loaded rGAs. The clear, randomly oriented, wrinkled-sheet structures of pristine rGAs shown in Figure a,b are consistent with the previous reports. , The wrinkled nature of the composites prepared with rGA500 was more prominent compared to rGA300 composites, consistent with its higher surface area and pore volume. With the impregnation of ILs, rGAs became smoother by losing their roughness as can be seen in Figure c,d for [BMPyr]­[DCA] and Figure e,f for [BMPyr]­[PF 6 ]-loaded rGAs.…”
Section: Resultssupporting
confidence: 91%
“…The clear, randomly oriented, wrinkled-sheet structures of pristine rGAs shown in Figure 2a,b are consistent with the previous reports. 41,42 The wrinkled nature of the composites prepared with rGA500 was more prominent compared to rGA300 composites, consistent with its higher surface area and pore volume. With the impregnation of ILs, rGAs became smoother by losing their roughness as can be seen in Figure 2c,d Structures of the composites were further analyzed by XRD to check whether there was a change in the pristine material's crystal structure after IL impregnation.…”
Section: Structural Characterizationmentioning
confidence: 62%
See 1 more Smart Citation
“…Graphene aerogel (GA), a promising porous material, is used to support nickel-based catalysts. Kocer et al 143 synthesized various GA-supported Ni catalysts by employing a series of Ni precursors; they concluded that the increase in the pH of the impregnation solution resulted in a smaller average particle size of the nickel particles and more homogeneous dispersion of nickel nanoparticles, which is beneficial for accelerating the catalytic reaction. In recent years, there have also been many studies on ammonia decomposition catalysts supported by natural clay with nickel.…”
Section: Effect Of the Support Onmentioning
confidence: 99%
“…The effect of the nickel precursor on the surface properties of Ni/KL-supported catalysts prepared from nickel nitrate, nickel acetylacetonate, and nickel phthalocyanine was explored in hydrogenation of citral at 5 MPa and 50 °C, demonstrating different nickel species distribution in the zeolite and giving as the main reaction products always citronellal and citronellol . The prominent effect of Ni precursors was demonstrated, however, for various processes, e.g., ammonia decomposition for the production of CO x -free hydrogen (nickel nitrate, nickel acetylacetonate), CO 2 methanation (nickel acetate, nickel nitrate, nickel acetylacetonate, nickel sulfate, and nickel chloride) including over zeolite 5A and 13X supported catalysts (nickel nitrate, nickel citrate, and nickel acetate), 1,1,1,2-tetrafluoroethane pyrolysis to trifluoroethylene (nickel acetate, nickel nitrate, and nickel chloride), steam and enhanced steam methane reforming (nickel acetate, nickel nitrate), glycerol steam reforming (nickel nitrate, nickel chloride, nickel acetate, and nickel acetylacetonate), hydroisomerization of n -decane (nickel nitrate, nickel acetylacetonate, and (triethylenediamine)-nickel nitrate), hydrogenation and ring-opening of tetralin (nickel nitrate, nickel citrate), where formation of different surface Ni 0 species, amount of acid sites, adsorption of coordinating anions, and Ni particles’ distribution depending on precursors were shown to directly affect Ni dispersion and accessibility. Therefore, the choice of the metal salt precursor can also be significant when designing Ni-based catalysts for citral hydrogenation.…”
Section: Introductionmentioning
confidence: 99%